2018
DOI: 10.1111/jphp.13011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Cymbopogon martinii essential oil on Cutibacterium (formerly Propionibacterium) acnes strains and its interaction with keratinocytes

Abstract: Objectives The human skin microbiota is mainly composed of bacteria belonging to the genera Staphylococcus, Cutibacterium, Micrococcus and Corynebacterium, but on the skin of the face and back, ca. 50% of the total microbiota is represented by the bacterium Cutibacterium acnes. The aim of this research was to evaluate the impact of C. martini EO and its major compound, geraniol, on C. acnes. Methods The minimum inhibitory concentration against C. acnes strains, phenotypic changes and responses of the proteome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Traditional medical plants and their extracts provide good choices for the treatment of C. acne and show excellent results in bacteriostasis research (Hamdy et al., 2017; Jeong and Kim, 2017; Poomanee et al., 2018). EOs from other plant extracts have good antimicrobial properties and they are valid against C. acne (Millerm A et al., 2015; Murbach Teles Andrade et al., 2018). Citrus EO contains a lot of bioactive substances (Dosoky and Setzer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional medical plants and their extracts provide good choices for the treatment of C. acne and show excellent results in bacteriostasis research (Hamdy et al., 2017; Jeong and Kim, 2017; Poomanee et al., 2018). EOs from other plant extracts have good antimicrobial properties and they are valid against C. acne (Millerm A et al., 2015; Murbach Teles Andrade et al., 2018). Citrus EO contains a lot of bioactive substances (Dosoky and Setzer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, searching for alternative antimicrobial compounds from natural materials is crucial. Previous studies found that essential oils from some plants, e.g., cloves, cacti, and tea trees, significantly inhibited the growth of C. acnes (Murbach Teles Andrade et al, 2018;Ossa-Tabares et al, 2020). There has not been any research attempting to investigate the antibacterial and antibiofilm activities of melanins against C. acnes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more attention has been paid to natural products derived from plants due to their higher efficacy and lower toxicity, which can replace or assist antimicrobial agents in inhibiting the proliferation of C. acnes ( De Canha et al, 2019 ; Di Lodovico et al, 2020 ; Wei et al, 2021 ). Accumulating evidence showed that many essential oils from plants such as cloves, cactus, tea tree, and so on possessed an inhibitory effect on C. acnes ( Fu et al, 2009 ; Murbach Teles Andrade et al, 2018 ; Ossa-Tabares et al, 2020 ). However, there is a lack of research on the mechanism underlying the antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%